Missed injuries during the initial assessment of trauma patients in red zone Emergency Department Hospital Universiti Sains Malaysia - Cariaga, Rozaimie (2020)
Introduction: Dealing with trauma patient in Emergency department (ED) is a major challenge. Despite a systematic initial assessment, the risk of missing injuries is still inevitable. This study is conducted to determine the incidence rate, evaluate the risk factors and described the injuries missed after initial assessment in red zone ED Hospital Universiti Sains Malaysia (Hospital USM). Materials & Methods: Hospital records of 485 patients presented to red zone over one-year period (June 2016 to May 2017) were retrospectively reviewed. Missed injuries (MIs) were defined as any new injury identified after disposition from ED to a period before hospital discharge which also includes injuries reported from formal radiological reports and injuries found after surgical exploration. A clinically significant MI is an injury that require operative treatment and injury with Abbreviated Injury Scale (AIS) ≥3. Results: There were 135 MIs were discovered in 94 patients with a prevalence of 19.4% and incidence rate of 2.75 per 100 person-hours. Most common involved body regions were the face (35%), followed by upper & lower extremities (20%), head (11%), thorax & abdomen (10% each), spine (9%). 46 injuries were clinically significant, but majority MIs were treated conservatively (81%). 46 % injuries were missed radiologically, 45% clinically and 9% intraoperatively. Patient who were intubated (p=0.007), had GCS ≤10 (p=0.022), had higher ISS score (p<0.001), transfused with blood within 24 hours (p=0.001) and stayed longer in ED (p=0.007) were associated with MIs. Conclusion: MI rate after initial assessment in ED Hospital USM is within the range of previous reported literatures. Strategies to reduce MIs should focus on active reassessment of a high-risk patients by ED team and by subsequent managing team as well as early radiological input.